2007
DOI: 10.1007/s11205-007-9086-6
|View full text |Cite
|
Sign up to set email alerts
|

Safe drinking water and satisfaction with environmental quality of life in some oil and gas industry impacted cities of Nigeria

Abstract: Sachet water, Borehole, Coliforms, Cities, Oil, Environment, Quality of life,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Because many sachet producers are small-scale cottage industries, Ghanaian regulatory agencies, such as the Food and Drugs Board and Ghana Standards Board, have had difficulty tracking the sachet industry's rapid growth and ensuring quality control. Recent research on sachet water has primarily focused on sub-standard quality and potential disease transmission in Ghana (Addo et al, 2009; Ampofo et al, 2007; Dodoo et al, 2006; Kwakye-Nuako et al, 2007; Obiri-Danso et al, 2003), and Nigeria (Adenkunle et al, 2004; Ejechi and Ejechi, 2008; Ifeanyi et al, 2006; Nwosu and Ogueke, 2004; Olaoye and Onilude, 2009; Onifade and Ilori, 2008; Orisakwe et al, 2006; Oyedeji et al, 2010), with some elaboration on health impact. Although not every study has found sachet water quality to be troublesome (Egwari et al, 2005; Olowe et al, 2005), there is generally a bias toward the publication of negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Because many sachet producers are small-scale cottage industries, Ghanaian regulatory agencies, such as the Food and Drugs Board and Ghana Standards Board, have had difficulty tracking the sachet industry's rapid growth and ensuring quality control. Recent research on sachet water has primarily focused on sub-standard quality and potential disease transmission in Ghana (Addo et al, 2009; Ampofo et al, 2007; Dodoo et al, 2006; Kwakye-Nuako et al, 2007; Obiri-Danso et al, 2003), and Nigeria (Adenkunle et al, 2004; Ejechi and Ejechi, 2008; Ifeanyi et al, 2006; Nwosu and Ogueke, 2004; Olaoye and Onilude, 2009; Onifade and Ilori, 2008; Orisakwe et al, 2006; Oyedeji et al, 2010), with some elaboration on health impact. Although not every study has found sachet water quality to be troublesome (Egwari et al, 2005; Olowe et al, 2005), there is generally a bias toward the publication of negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…In all these, however, little work has been done regarding environmental QoL in communities where natural resource prospecting and extraction activities are taking place (Ejechi and Ejechi 2008). More importantly, integration of community perceptions and expectations and social impact of proposed development activities into environmental QoL studies have also been lacking in Nigeria.…”
Section: Overview Of Qol Research In Nigeriamentioning
confidence: 99%
“…The supply of drinking water in many cities of the developing world is unreliable, leaving large sections of city populations (particularly the urban poor) unserved (Boadi et al . ; Ejechi & Ejechi ). In Nigeria, private borehole operators and sachet drinking water producers have largely replaced municipal water supplies as a source of drinking water (Ejechi & Ejechi ).…”
Section: Introductionmentioning
confidence: 99%
“…; Ejechi & Ejechi ). In Nigeria, private borehole operators and sachet drinking water producers have largely replaced municipal water supplies as a source of drinking water (Ejechi & Ejechi ). For example, nearly 70% of the population in Lagos State, Nigeria, rely on drinking water supplies sourced from independent sources (Coker ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation